Educational Governmental Order As An Administrative Contract: Argumentation Of Its Nature, Application Prospects In Ukraine - Юрчишин, Василь Миколайович; Юрчишин В. М.; Юрчишин, Василий Николаевич; Yurchyshyn, Vasyl M.; Пивовар, Юрій Ігорович; Пивовар, Ю. І.; Пивовар, Юрий Игоревич; Pyvovar, Yurii I.; Pyvovar, Yuriy; Миколенко, Олександр Іванович; Миколенко, О. І.; Миколенко, Александр Иванович; et al. (IJSTR, 2019)
Issue of the legal nature of contracts concluded in the process of educational governmental order is socially necessary, first of all, for all participants of this process to know norms of which branches of law to use or apply in the exercising and especially protection (defense) of their constitutional rights. The purpose of this article is to prove the administrative and legal nature of the contracts concluded in the process of formation, placement and performance of the educational governmental order. The research methodology was formed on the normative concept and the contractual concept of the administrative law. Authors are proved that in the event of disputes when concluding and performing contracts on educational governmental order, the administrative and legal procedures of public law shall be applied to resolve the conflict. Based on the purpose of the institute of educational governmental order, we consider it expedient to change the principles of formation of relations between a governmental customer, educational institution (a performer of the governmental order), a degree-seeking student, focusing on the main idea "invested state funds should be returned to the customer in the form of a benefit (profit) that contributes to meeting a specific state need)."

Питання юридичної природи договорів, укладених у процесі освітнього державного замовлення, є суспільно необхідним, перш за все, для того, щоб усі учасники цього процесу знали, норми яких галузей права використовувати або застосовувати при здійсненні та особливо охорони (захисті) їхніх конституційних прав. Метою цієї статті є доведення адміністративно-правової природи договорів, що укладаються в процесі формування, розміщення та виконання освітнього державного замовлення. Методологія дослідження сформована на нормативній концепції та договірній концепції адміністративного права. Авторами доведено, що у разі виникнення спорів при укладенні та виконанні договорів освітнього державного замовлення для вирішення конфлікту застосовуються адміністративно-правові процедури публічного права. Виходячи з призначення інституту освітнього державного замовлення, вважаємо за доцільне змінити принципи формування відносин між державним замовником, закладом освіти (виконавцем державного замовлення), здобувачем вищої освіти, орієнтуючись на основну ідею «інвестовані державні кошти мають бути повернуті замовнику у вигляді вигоди (прибутку), що сприяє задоволенню конкретної державної потреби)».
Pyvovar Y. Educational Governmental Order As An Administrative Contract: Argumentation Of Its Nature, Application Prospects In Ukraine / Y. Pyvovar, O. Mykolenko, A. Detiuk, V. Yurchyshyn, P. Olena // International Journal of Scientific and Technology Research. - Vol. 8. - Iss. 11. - IJSTR, 2019. – P. 595-602.
Keywords: administrative dispute; administrative contract; educational governmental order; educational state contract; educational state needs; higher education; адміністративний спір; адміністративний договір; освітнє державне замовлення; освітній державний контракт; освітні державні потреби; вища освіта; Research Subject Categories::LAW/JURISPRUDENCE